2007
DOI: 10.1111/j.1742-1241.2007.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

An intensive group therapy programme for smoking cessation using nicotine patch and internet mailing supports in a university setting

Abstract: This study suggests that our programme in a university setting seems to be effective mainly because of peer-supports among the participants through regular face-to-face meetings and their own mailing supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The study with the greatest intervention effect also had the highest intervention adherence rate [31]. In this study, 50% quit rate was achieved among University staff who participated in a multi-component cessation program.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The study with the greatest intervention effect also had the highest intervention adherence rate [31]. In this study, 50% quit rate was achieved among University staff who participated in a multi-component cessation program.…”
Section: Resultsmentioning
confidence: 59%
“…Among the randomized studies, 16 were largely internet-based[13][28], while the other 2 were multi-component studies[29], [30]. Similarly, 2 of the 10 interventions (11 studies) in the pre-post group had multiple components[31], [32], while the others were largely internet-based [12], [33][40]. Summary of the studies included in the review categorized according to the two main designs used can be found in tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful employer-based cessation programmes generally take two approaches, linking them to policies such as workplace smoking bans,64 65 and offering incentives to quit such as free NRT 66 67. Learning from earlier studies on incentives,68 some employers combine monetary incentives with counselling 69 70.…”
Section: Population Cessation: Interventions Consideredmentioning
confidence: 99%
“…In accordance to the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) Article 14, governments should make smoking cessation easily accessible for would-be quitters. Unfortunately, only a quarter of the 181 WHO FCTC signatories have designated budgets for smoking cessation 14 . Tobacco control interventions have had a positive outcome in high-income Asian countries such as Japan, South Korea and Singapore, but the results have not been replicated in low- and middle-income countries such as China and India 15 .…”
Section: Introductionmentioning
confidence: 99%